Pengaruh Tingkat Kepuasan Pelanggan Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Ulang Di Aulia Cell - Dinda Aulia Karenina; Anggun Pagestu; Arifudin Arifudin (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This research aims to determine the influence of Customer Satisfaction Level and Service Quality on Repurchase Decisions at Aulia Cell. Data collection was carried out using primary data sources obtained through distributing online questionnaires via Google Form to students. The type of research used is quantitative research. The number of samples determined in this research was 50 respondents. The research data collection method was carried out through distributing questionnaires using a four-point Likert scale as a measuring tool. The data analysis technique in this research uses multiple linear analysis with a model feasibility test (F test) and partial regression test (t test). The data processing was carried out using the Statistical Package for Social Science (SPSS) 26 program. The results of this research show that there is a significant influence on the level of customer satisfaction and service quality on repeat purchase decisions at Aulia cell.